YUDISIALISASI POLITIK: PERAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN MASALAH KONSTITUSIONALITAS UNDANG-UNDANG PEMILIHAN UMUM - I Wayan Budha Yasa (Jurnal Komunikasi Hukum, 2023)
This article will be discussed in general about judicialization of politics at the theoretical and practical level in the Indonesian context. Meanwhile, in particular, this article will discuss the role of the Constitutional Court in solving the problem of the constitutionality of the Electoral Law using the concept of judicialization of politics. The purpose of the discussion is to find out for sure whether the role of the Constitutional Court is only limited to resolving the issue of the constitutionality of the Electoral Act or is more likely to show the practice of judicialization of politics. Normative research methods are used for the purposes of this research by prioritizing a case and conceptual approach to analyze the legal materials used. The legal materials collected as a support for this research are then qualitatively constructed and presented descriptively. Based on the results of the discussion, it is known that the practice of judicialization of political dissemination in Indonesia can be seen in the decisions of the Constitutional Court regarding the resolution of the constitutionality of the Electoral Law. The existence of a requirement from the Constitutional Court in determining the unconstitutionality of the provisions of the Electoral Act as contained in the decisions of the Constitutional Court, indicates that the power of the law has entered to regulate the political process. Thus, the role of the Constitutional Court is not only limited to solving the issue of the constitutionality of the Electoral Act, but tends to show the practice of judicialization of politics.